Nowa „chłopomania” czy próba odczytania Chłopów z perspektywy feministycznej? .......... 255 - Packalén Parkman, Małgorzata Anna (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
A NEW “PEASANT-MANIA” OR AN ATTEMPT TO READ REYMONT’S PEASANTS FROM A FEMINIST PERSPECTIVE?Today’s teachers of Polish culture to foreigners face many pedagogical glottodidactic challenges and one of them centers on how to present early Polish literature to a young generation of learners in Sweden. The case in point is an attempt to introduce students to the broad subject matter of Reymont’s novel Peasants (1904–1909). His work does not appeal to the imagination of contemporary Swedish youth neither in terms of the work’s rural subject matter nor in its linguistic and stylistic layout. The situation was very similar in Poland for many years but in the 1960s and 1970s the rustic life acquired a new role: it became a tool with which students could reconstruct and evoke certain universal features of human history. The most recent example of a successful methodological approach to the novel is its last year’s film adaptation The Peasants (2023), in which the women’s world is presented from a feminist perspective. This new cinematic reading of Reymont’s Peasants allows students to see the Polish classic literature as being still engaging and universal. This article discusses both: the result of applying the feminist perspective and the film’s critical reception in Poland and abroad.